2009
DOI: 10.1370/afm.946
|View full text |Cite
|
Sign up to set email alerts
|

Pay for Performance in Primary Care in England and California: Comparison of Unintended Consequences

Abstract: PURPOSEWe undertook an in-depth exploration of the unintended consequences of pay-for-performance programs In England and California. METHODSWe interviewed primary care physicians in California (20) and England (20) and compared unintended consequences in each setting. Interview recordings were transcribed verbatim and subjected to thematic analysis. RESULTSUnintended consequences reported by physicians varied according to the incentive program. English physicians were much more likely to report that the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
146
1
6

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 29 publications
1
146
1
6
Order By: Relevance
“…Studies of unintended consequences of indicators used in such schemes have shown they can lead to changes in the nature of the consultation/office visit, threats to the physician-patient relationship, and threats to professional autonomy. 3 Implications for practice and research The current QOF depression severity indicators (DEP4 and DEP5) incentivise routine use of structured assessment tools to assess depression severity at diagnosis and follow-up. This systematic review shows that it is very uncertain whether this leads to improved health outcomes for patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of unintended consequences of indicators used in such schemes have shown they can lead to changes in the nature of the consultation/office visit, threats to the physician-patient relationship, and threats to professional autonomy. 3 Implications for practice and research The current QOF depression severity indicators (DEP4 and DEP5) incentivise routine use of structured assessment tools to assess depression severity at diagnosis and follow-up. This systematic review shows that it is very uncertain whether this leads to improved health outcomes for patients.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…2 However, it is important that indicators have an evidence base to support their use and that any potential unintended consequences are identified and rectified, otherwise they may have adverse effects on care. 3 Depression is a major cause of chronic ill-health and is largely managed in primary care. 4,5 Two indicators in the depression domain of the QOF are related to depression severity assessment: one at diagnosis and one at follow-up.…”
Section: Introductionmentioning
confidence: 99%
“…The literature suggests that incentive payments have led to mixed results across various jurisdictions, [3][4][5][6] including the Quality and Outcomes Framework in England, [7][8][9][10][11] and in Canada. 12,13 Furthermore, the term pay for performance can have a range of meanings.…”
Section: Evaluation Of Incentive Payments and The Incentive Programmentioning
confidence: 99%
“…We know from earlier research that physicians' performance can be changed, for better or for worse, based on financial incentives. 2 The most illustrative example of financially motivated behavioral changes comes from a 2004 United Kingdom (UK) experiment. Family medicine physicians were incentivized to adhere to 136 clinically based core measures, known collectively as the Quality and Outcomes Framework.…”
mentioning
confidence: 99%